(untitled) (American Journal of Islam and Society, 2006)
Jordan has existed now for nearly 60 years, since the termination of the British mandate in 1946, and has generally been studied in terms of its Hashemite rulers and the “King’s men,” those who helped the Hashemites construct it. These historical narratives, argues Anderson, have privileged the Jordanian monarchy and the “high” elements of society and, consequently, have ignored the “urban” elements that played an equal, if not a greater, role in constructing the Jordanian national identity. In this sense, Anderson gives voice to narratives that were previously unknown and unheard and, by so doing, makes a significant contribution to the body of literature on Jordan. She contends that the “Arab Street” “holds a key to understanding Jordan in the twentieth century” and, in this regard, focuses upon the “true” Jordanian natives and their narrative. Taking a subaltern approach to Jordanian history, she examines the foundation of the Jordanian National Movement (JNM), a coalition of leftist parties based loosely upon Arab nationalism, and its influence upon the nation’s formation. Given her unique approach to Jordanian history, she admits that her work is incomplete, for many first-hand accounts and memoirs, which cannot be found, should be examined in light of the larger body of literature on Jordan. The history of Jordan is that of post-colonial independence and nationhood, of a nation that had never existed in the hearts and minds of those who would live within its borders until it was actually drawn on a map. In an agreement brokered in late March 1921 between Winston Chuchill, then the British colonial secretary, and Abdullah I, the latter would accept British ...